National 30-Day Outcomes for Posterior Cranial Vault Distraction. Issue 3 (May 2019) - Chouairi, Fouad; Torabi, Sina J.; Alperovich, Michael
Abstract : Background: Posterior vault distraction (PVD) can rapidly expand calvarial volume in infancy. Limited data exist regarding its perioperative and postoperative safety profile. This study sought to investigate the patient profile, outcomes, and safety of PVD using a national pediatric database. Methods: Posterior vault distraction patients between 2012 and 2016 were isolated from the National Surgical Quality Improvement Program Pediatric database. Patient background, perioperative outcomes, and risk factors were analyzed using chi-squared, t test analysis, and multivariate regression. Results: Ninety-four patients who underwent PVD were isolated with 67 ultimately meeting inclusion criteria for the study. The majority of patients undergoing PVD had limited other documented comorbidities. No patients required reoperation or 30-day readmission. There were no incidences of stroke, surgical site infection, or death. Subdividing outcomes by specialty, plastic surgeons performed PVD on significantly older patients than neurosurgeons (188 days vs 138 days, P = 0.008). Increasing age was associated with increasing operative time ( P < 0.001). Furthermore, increasing age is associated with greater absolute transfusion requirements ( P = 0.018) and higher, but not significant, risk of requiring any volume of blood transfusion ( P = 0.105). Conclusions: Posterior vault distraction is a safe procedure to rapidly expand calvarial volume in the setting of craniosynostosis. Increasing patient age is the strongest predictor for prolonged operative time and higher blood transfusion volumes.